RESPONSIBILITY FOR THE MANAGEMENT OF REGIONAL WEALTH SEPARATED FROM REGIONAL OWNED ENTERPRISES IN INDONESIA - Nurakhman; Richard (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
The administration of segregated local assets within Regional-Owned Enterprises (BUMD) serves as a vital mechanism for attaining fiscal autonomy at the regional level; yet, its inherent intricacies often precipitate grave concerns over responsibility and openness. This investigation seeks to evaluate the responsibility framework governing segregated local assets in BUMD, pinpoint discrepancies between statutory mandates and implementation realities, and propose an optimal responsibility paradigm. Adopting a normative juridical methodology incorporating statutory and conceptual perspectives, the study relies on library-based inquiry for data gathering. Key discoveries highlight three core issues: firstly, deficiencies in BUMD's internal control apparatus permit irregularities to evade early detection; secondly, notable inconsistencies prevail between BUMD responsibility rules and financial disclosure routines, fostering juridical vulnerabilities; thirdly, an inadequate assessment process reliant on quantifiable metrics results in subdued and erratic contributions from segregated local assets to Regional Original Revenue. Enhancing internal controls, aligning regulatory standards, and developing a holistic performance appraisal structure emerge as the foremost remedies to foster responsible and fair BUMD administration.